Building effective employment programs for unemployed youth in the Middle East and North Africa - Angel-Urdinola, Diego F. (Directions in development, 2013)
Given the labor market challenges that countries in the Middle East and North Africa (MENA) region are facing (notably high unemployment, prevalence of skills mismatches, low labor market mobility, and lack of formal employment networks), employment services could be a relevant policy instrument to assist unemployed individuals to find jobs. Despite high and increasing unemployment rates, employers in the region are facing difficulties to find workers whose competences and skills fit their employment needs. The study first surveys international best practices for the delivery of employment services and then reviews the provision of these services in a selected group of countries in the MENA region, with a focus on public provision through existing public employment agencies. Findings indicate public agencies in the region face many challenges for the effective delivery of employment programs, namely poor administrative capacity,system fragmentation, lack of governance and accountability, regulation bottlenecks, and flaws in program design. In order to help unemployed workers to obtain the competences required by available jobs, this study proposes a reform agenda based on the development of strong partnerships between public agencies, public providers, and employers for the design and implementation of flexible employment programs that respond to real employment needs. These partnershipss will need to be developed with strong governance mechanisms that make beneficiaries, private providers, and firms accountable for making sure that investments in employment programs lead to employment insertion. The book is directed to policy makers, practitioners, economists, and anyone interested in international best practices to promote a more effective delivery of employment services.